Law Enforcement Against Foreign Nationals as Perpetrators of Online Lending - Anak Agung Ngurah Adhi Wibisana; I Nyoman Gede Sugiartha; Anak Agung Sagung Laksmi Dewi (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2026)
Purpose: This study analyzes the legal regulation of foreign nationals within the Indonesian legal system and the sanctions imposed on them as perpetrators of online lending activities. Research Methodology: This research employs a normative legal approach using statutory, conceptual, and case analyses. Legal materials are examined qualitatively through literature review and deductive reasoning. Results: The findings show that foreign nationals are recognized as legal subjects under the principle of territorial jurisdiction and are subject to Indonesian law when conducting legal acts within its territory. Sanctions for involvement in online lending may include civil liability for breach of contract and unlawful acts under the Civil Code, criminal penalties, and administrative measures such as immigration sanctions. Conclusions: Indonesian positive law provides a sufficient legal framework to impose civil, criminal, and administrative sanctions on foreign nationals engaged in online lending. However, enforcement remains limited by practical constraints. Limitations: This study focuses on existing regulations and court decisions and does not examine international legal cooperation mechanisms in depth. Contributions: This study contributes to the literature by offering an integrated analysis of the legal position of foreign nationals in Indonesia’s online lending regulation.